The moderating effect of IT capability on the relationship between business process reengineering factors and organizational performance of banks - Ringim, Kabiru Jinjiri; Razalli, Mohd Rizal; Hasnan, Norlena (ARRAY Development, 2012)
The objective of this paper is to investigate the moderating effect of IT capability in the relationship of Business Process Reengineering (BPR) factors and the organizational performance.BPR factors are operationalized by change management, BPR strategy alignment, customer focus, management commitment, IT investment, and adequate financial resources.The IT capability includes IT knowledge, IT operations and IT objects.Data was collected through a hand-delivery method by sending questionnaires to 560 banks (Commercial, Microfinance and Mortgage). This study used stratified random samplings proportionate to the numbers of the banks for sample selection.The findings showed that IT capability moderated the relationship between BPR factors such as change management, customer focus, management commitment and overall organizational performance of the bank.Furthermore, the result revealed that IT capability moderated the relationship between IT investment, management commitment and customer service management performance.The outcome of this study provides important insight to researchers for understanding on the effects of BPR factors and IT capability on organizational performance.